Aglomerações industriais e polos econômicos regionais: uma análise comparativa entre a Região Sul do Brasil e a Província do Québec/CA - Barchet, Isabela (2016)
This research is a comparative analysis of industrial agglomerates and polarization in Southern Brazil and Quebec Province in Canada. Thus, the research analyzed the spatial configuration of productive activities agglomerations in Southern Brazil and in Quebec Province in Canada in order to promote elements for discussion of regional effects this process of concentration. Specifically, the study discussed the elements that influence the formation of agglomerates industrial; identified the industrial agglomerates in Quebec Province and in the states of Southern Brazil and sought to understand the effects of industrial concentration process in the perspective of winners and losers regions. It was used as methodological procedure a multiple regression model with panel data, the estimate of the Location Quotient (QL) with filters and some statistical parameters as, for example, the Pearson Asymmetry Coefficient and the Gini Concentration Coefficient, for a discussion of drive and dynamics of industrial employment. The results showed that the social capital, physical and financial, as well as the market potential are determining factors for the formation of industrial agglomerates. In relation to industrial agglomerates, the study identified to Santa Catarina 56 productive agglomerations for the year 2013. Representing an increase of 30% of agglomerates compared to 2006, as well as a slight diversification in the state's productive structure. In Rio Grande do Sul were identified 65 industrial agglomerates distributed in 16 sub-sectors and in Paraná, between 2006 and 2013, there was a increase of 20% in the number of industrial agglomerates. For Québec Province were identified 6 industrial groupings divided into 4 sub-sectors for 2012, representing a reduction of 33% in the number of agglomerates identified for 2005. Finally, it was noted a distribution of industrial employment toward spaces that, in some cases are located relatively far from areas with the initial presence of the industrial sector. It stayed evident to the southern Brazil, that the largest gains in relation to the industrial employment can not be attributed to large urban centers, or more specifically, the big metropolitan areas.